Work-related thumb disorders in South African physiotherapists treating musculoskeletal conditions using manual therapy techniques - Heather Jenkins; Hellen Myezwa (AOSIS, 2015)
Research question: What is the prevalence of and factors associated with work-related thumb problems (WRTP) in South African physiotherapists treating musculoskeletal conditions using manual therapy techniques? Design: A cross-sectional, descriptive study design was used and data were collected using two Internet-based questionnaires. Participants: The sample size calculated for the study was 284 using 95% confidence levels and a 5% margin of error. There were 395 participants that were included in the study. Outcome measures: The variables measured included demographic, employment, educational and occupational factors. Results: The lifetime prevalence of WRTP in the physiotherapists was 65.3%. The manual techniques that were significantly associated with WRTP in the respondents who reported thumb problems were all grades of transverse glides applied to the spine as well as grade II-IV unilateral and central posterior-anterior pressures to the spine. The factors that remained significantly associated with WRTP in all 395 respondents after regression analysis were the cervical treatment of up to six patients a day and hyperextension > 30° of the non-dominant interphalangeal (IP) joint of the thumb. Conclusion: This study confirms that a high percentage of physiotherapists using manual therapy techniques to treat musculoskeletal conditions are experiencing WRTP. Recommendations: The development of a valid and reliable WRTP screening tool is needed to aid in the identification of physiotherapists at risk and thus in the primary prevention of WRTP. A longitudinal study which follows newly qualified physiotherapists is recommended to investigate a possible cause-effect relationship and preventative strategies for WRTP in physiotherapists.